2008
DOI: 10.1126/science.1151153
|View full text |Cite
|
Sign up to set email alerts
|

Using Engineered Scaffold Interactions to Reshape MAP Kinase Pathway Signaling Dynamics

Abstract: Scaffold proteins link signaling molecules into linear pathways by physically assembling them into complexes. Scaffolds may also have a higher-order role as signal-processing hubs, serving as the target of feedback loops that optimize signaling amplitude and timing. We demonstrate that the Ste5 scaffold protein can be used as a platform to systematically reshape output of the yeast mating MAP kinase pathway. We constructed synthetic positive- and negative-feedback loops by dynamically regulating recruitment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
340
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 322 publications
(348 citation statements)
references
References 35 publications
7
340
0
1
Order By: Relevance
“…Next we investigated how circuit dynamics behave when parameter values change, leading, in particular, to a bifurcation where the system transitions from one dynamical regime to another. Recent work showed that bifurcations from excitable to other dynamical regimes, such as oscillatory or bistability, are possible for a bacterial cellular differentiation circuit and yeast mating MAP kinase pathway in vivo (18,46). Similarly, for the model system described in this study, changes in various parameter values can induce bifurcations.…”
Section: Effect Of Noise On Activator-repressor Circuit Dynamics Near Amentioning
confidence: 98%
“…Next we investigated how circuit dynamics behave when parameter values change, leading, in particular, to a bifurcation where the system transitions from one dynamical regime to another. Recent work showed that bifurcations from excitable to other dynamical regimes, such as oscillatory or bistability, are possible for a bacterial cellular differentiation circuit and yeast mating MAP kinase pathway in vivo (18,46). Similarly, for the model system described in this study, changes in various parameter values can induce bifurcations.…”
Section: Effect Of Noise On Activator-repressor Circuit Dynamics Near Amentioning
confidence: 98%
“…Synthetic gene networks, on the other hand, are rationally designed and constructed to realize core topological modules of GRN in vivo without interference from auxiliary connections. They can therefore be studied in isolation to greater detail and reveal novel insights into the design and working of biological systems and processes (15), such as gene expression noise (4,(16)(17)(18)(19)(20)(21), multistability (8,10,22), oscillations (23)(24)(25)(26), intracellular signaling (27,28), intercellular communications (29,30), and multicellular pattern formation (31,32).…”
mentioning
confidence: 99%
“…In the context of synthetic biology (8)(9)(10)(11)(12)(13)(14)(15), signaling represents a challenging case because pathway modification requires protein reengineering or de novo design. Both are hard tasks, but progress has been steady (1,(16)(17)(18)(19).…”
mentioning
confidence: 99%